Return to sport after arthroscopic rotator cuff repair of full-thickness rotator cuff tears: A systematic review - Alben, M. G.; Gambhir, N.; Papalia, A. G.; Bostrom, N.; Larose, G.; Virk, M. S.; Rokito, A. S. (Clinical Journal of Sport Medicine, 2023)
Objective: Perform a systematic literature review regarding return to sport (RTS) outcomes after arthroscopic rotator cuff repair (aRCR) for full-thickness rotator cuff tears (FTRCTs).